New pathological findings in emphysema of childhood: 2. Overinflation of a normal lobe. Issue 2 (March 1971) - Hislop, Alison; Reid, Lynne
Abstract : A quantitative study of the structure of the affected lobe from a patient with childhood lobar emphysema is here reported. The left upper lobe was removed from a child aged 2½ months who was suffering from acute respiratory distress and showing on his radiograph hypertransradiancy of the left lung. At operation the lobe was found to be increased in volume and rotated through 180° on its pedicle. After laboratory injection of some of the pulmonary artery branches and distension of the lobe, the stage of development of the various lung structures was studied quantitatively. The arteries and bronchi were normal in number and structure: the alveolar number was normal for the age of the child but the volume of an alveolus was increased four to five times, as was total lung volume. The antenatal development of this lobe was normal and it seems that the emphysema could have followed the rotation of the lobar hilum, although no cause for this rotation was found.